Symbolism in the Short Stories of Anwar Sajjad - Hameed Khan, Shaista; Kausar, Rehana; Imran, Muhammad (sourcecoder, 2022)
Anwar Sajjad is an important name of Urdu short stories. He wrote romantic short stories using symbols and metaphors. But after some time this symbolic color was sharpest. He also tried to match the controversial signs from the symbols. He also tried to combine mythological stories with symbols. Through the sinners and symbols, themes of oppression, oppression, humiliation and themes like human and moral values have presented. In this article, the symbolism in fictions of the Anwar Sajjad is described.